The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/life13020322
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation as Prognostic Hallmark of Clinical Outcome in Patients with SARS-CoV-2 Infection

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is often characterized by a life-threatening interstitial pneumonia requiring hospitalization. The aim of this retrospective cohort study is to identify hallmarks of in-hospital mortality in patients affected by Coronavirus Disease 19 (COVID-19). A total of 150 patients admitted for COVID-19 from March to June 2021 to “F. Perinei” Murgia Hospital in Altamura, Italy, were divided into survivors (n = 100) and non-survivors groups (n = 50). Blood counts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Before swallowing, the maximal quantity of saliva in the oral cavity was 1.19 mL and 0.96 mL for males and females, respectively [ 53 ]. Under normal circumstances, human saliva forms a physical barrier, a film, and prevents direct contact between the tooth enamel surface and acidic beverages, thus protecting teeth from erosive attack by acids [ 45 , 84 , 85 , 86 ]. However, the erosion tests were carried out without saliva [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Before swallowing, the maximal quantity of saliva in the oral cavity was 1.19 mL and 0.96 mL for males and females, respectively [ 53 ]. Under normal circumstances, human saliva forms a physical barrier, a film, and prevents direct contact between the tooth enamel surface and acidic beverages, thus protecting teeth from erosive attack by acids [ 45 , 84 , 85 , 86 ]. However, the erosion tests were carried out without saliva [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Germ-free mice, raised in sterile conditions without exposure to microorganisms, have been used as experimental models to study the impact of germ-free mice on bone density and structure. Microbiota transplantation studies have shown that introducing a diverse and healthy microbiota positively affects bone health in recipients, while transplanting from diseased or imbalanced donors may lead to compromised bone density and structure [20][21][22][23][24]. In human trials, probiotics have been found to modulate the GM, with certain strains associated with increased calcium absorption and improved bone density.…”
Section: Experimental Evidence Of the Impact Of The Gastrointestinal ...mentioning
confidence: 99%
“…Five of the papers of the Special Issue focus on the general and specific conditions of COVID-19 pathology [ 29 , 30 , 31 , 32 , 33 ]: one paper explored the potential role of inflammation as a prognostic hallmark of clinical outcome in infected patients. The main objective of a second study was to describe the role of host genetic variability in modulating COVID-19 clinical outcomes.…”
Section: General and Specific Condition Of Pathologymentioning
confidence: 99%